On‐Chip Electrical Monitoring of Real‐Time "Soft" and "Hard" Protein Corona Formation on Carbon Nanoparticles. Issue 7 (20th April 2020) - Srivastava, Indrajit; Khan, Muhammad S.; Dighe, Ketan; Alafeef, Maha; Wang, Zhen; Banerjee, Tuseeta; Ghonge, Tanmay; Grove, Lauren M.; Bashir, Rashid; Pan, Dipanjan
Abstract: When nanoparticles encounter a biological fluid, proteins, lipids, and other biomolecules adsorb on the nanoscale surface consequently leading to the evolution of a protein shell or "corona." The corona formed is dynamic in nature and depends on the "synthetic identity" of the NPs, ultimately affecting their biological response. In this paper, an integrated microfluidic platform coupled with an electrical resistance measurement setup is developed to monitor and investigate the real‐time formation of a biomolecular corona of carbon nanoparticles. "Soft" and "hard" corona formation stages are effectively discriminated based on their nanoscale surface chemistries when combined with a time‐frequency tool known as wavelet transform and machine‐learning techniques. Additionally, the corona and its composition are studied using different techniques such as dynamic light scattering, nanoparticle tracking analysis, zeta potential, excitation–emission profiles, 1D sodium dodecyl polyacrylamide gel electrophoresis and subsequently, liquid chromatography‐mass spectrometry analysis. The dynamic setup can eventually be used as a valuable tool for screening of any nanoparticles formulations with distinct surface chemistries for the purpose of reduced protein adsorption/weaker protein corona formation and consequently enhance the success of targeted drug delivery. Abstract : An integrated microfluidic platform coupled with electrical resistance measurement setup aided with wavelet transform and machine learning algorithms is developed to monitor the real‐time formation of protein corona and discrimination of their fouling behavior based on nanoscale surface chemistries.